2021
DOI: 10.18662/rrem/13.2/432
|View full text |Cite
|
Sign up to set email alerts
|

Formation Of Skills To Visualize Of Future Physics Teacher: Results Of The Pedagogical Experiment

Abstract: It is relevant for teachers of science to get visualization skills for explaining abstract concepts, showing the logic of processes, and explaining the natural phenomena at the micro and macro levels. For research conducting, authors used theoretical and empirical methods such as analysis of specialized for physics visualization software; survey for determining the needs of physics teachers; analysis of the curricula content for the training of future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…Han & Kim (2020), Ernest et al (2019), Yang et al (2021), Copur-Gencturk & Doleck (2021), Morze et al (2022), Astafieva et al (2019), Semenikhina et al (2021) works on the problem of development of mathematical competencies. Borrell (2006), Niss & Højgaard (2019) outline the main aspects of mathematical competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Han & Kim (2020), Ernest et al (2019), Yang et al (2021), Copur-Gencturk & Doleck (2021), Morze et al (2022), Astafieva et al (2019), Semenikhina et al (2021) works on the problem of development of mathematical competencies. Borrell (2006), Niss & Højgaard (2019) outline the main aspects of mathematical competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physics concepts that contain abstract phenomena require teaching media that can visualize these phenomena (Wibowo et al, 2017). A survey conducted by Semenikhina et al (2021) on physics teachers shows that computer simulations are needed such as Phet, VirtuLab, LabVIEW, and others to explain abstract phenomena. This survey is further strengthened by research conducted by Bajpai & Kumar (2015), which states that the use of computer simulations such as Phet, Crocodile Physics, and Edison 4.0 can help students better understand abstract concepts.…”
Section: Figure 6 Students' Average Scores On Each Aspect Of Visualiz...mentioning
confidence: 99%
“…This is in line with research conducted by Semenikhina. He investigated the opinion of physics teachers (48 teachers) regarding the use of software in physics lessons and found that the ability of teachers to develop computer visual models independently was only around 48% [7].…”
Section: Introductionmentioning
confidence: 99%